Paola Solombrino, The in house providing as a self-organization model for the public administration (Zamówienia in-house jako element modelu samoorganizacji administracji publicznej), „The Juridical Current” („Le Courant Juridique”) vol. 79, December 2019 - Różowicz, Konrad (Studia Prawa Publicznego, 2020)
Paola Solombrino, The in house providing as a self-organization model for the public administration (Zamówienia in-house jako element modelu samoorganizacji administracji publicznej), „The Juridical Current” („Le Courant Juridique”) vol. 79, December 2019